2009
DOI: 10.1103/physrevc.79.034306
|View full text |Cite
|
Sign up to set email alerts
|

Odd-even mass differences from self-consistent mean field theory

Abstract: We survey odd-even nuclear binding energy staggering using density functional theory with several treatments of the pairing interaction including the BCS, Hartree-Fock-Bogoliubov, and the HartreeFock-Bogoliubov with the Lipkin-Nogami approximation. We calculate the second difference of binding energies and compare with 443 measured neutron energy differences in isotope chains and 418 measured proton energy differences in isotone chains. The particle-hole part of the energy functional is taken as the SLy4 Skyrm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
199
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(205 citation statements)
references
References 64 publications
(101 reference statements)
5
199
1
Order By: Relevance
“…[60], one may argue that the standard Skyrme functionals, such as unedf0 and unedf1, lack the capability to describe many-body Coulomb effects; (ii) The explicit contribution of the Coulomb field to the pairing channel [67,68] is not taken into account. It is expected that separate pairing strengths for neutrons and protons, as in unedf1, will partly account for this missing contribution [35]. However, the existence of nontrivial correlations between pairing strengths and other parameters of the functional (see Table III) may have consequences for observables such as two-proton separation energies.…”
Section: Performance Of Unedf1 a Global Mass Tablementioning
confidence: 99%
See 1 more Smart Citation
“…[60], one may argue that the standard Skyrme functionals, such as unedf0 and unedf1, lack the capability to describe many-body Coulomb effects; (ii) The explicit contribution of the Coulomb field to the pairing channel [67,68] is not taken into account. It is expected that separate pairing strengths for neutrons and protons, as in unedf1, will partly account for this missing contribution [35]. However, the existence of nontrivial correlations between pairing strengths and other parameters of the functional (see Table III) may have consequences for observables such as two-proton separation energies.…”
Section: Performance Of Unedf1 a Global Mass Tablementioning
confidence: 99%
“…The value ρ c =0.16 fm −3 is used throughout this paper. We allow for different pairing strengths for protons (V p 0 ) and neutrons (V n 0 ) [35]. A cut-off of E cut = 60 MeV was used to truncate the quasi-particle space [36].…”
Section: Theoretical Framework a Time-even Skyrme Energy Densitymentioning
confidence: 99%
“…The authors of Ref. [55] considered that the overestimation in spherical nuclei may be partly attributed to the effect of the particle number fluctuation. They showed that the HFB calculation with the approximate particle number projection using the Lipkin-Nogami method improves the agreement with experiment for spherical nuclei.…”
Section: Choice Of V0mentioning
confidence: 99%
“…It is an open problem to construct the pair-DF which allows us to describe the pairing properties along the chains of semi-magic nuclei at the same quality achieved for deformed region [55,56,57]. The authors of Ref.…”
Section: Choice Of V0mentioning
confidence: 99%
“…Several groups are pursuing these calculations, e.g., those in Refs. [105][106][107][108][109][110][111][112]123], and many open questions remain as, e.g. how well one can treat paring in nuclear matter.…”
Section: The Nuclear Chart Varieties Of Elementsmentioning
confidence: 99%